A γ-adducin cleavage fragment induces neurite deficits and synaptic dysfunction in Alzheimer's disease. (August 2021) - Xiong, Min; Zou, Li; Meng, Lanxia; Zhang, Xingyu; Tian, Ye; Zhang, Guoxin; Yang, Jiaolong; Chen, Guiqin; Xiong, Jing; Ye, Keqiang; Zhang, Zhentao
Highlights: AEP age-dependently cleaves γ-adducin at N357 in AD. The AEP-generated γ-adducin (1-357) fragment translocates into nucleus and inhibits neurites growth. γ-adducin (1-357) fragment induces neurites deficits and synaptic dysfunction by downregulating Rac2. γ-adducin (1-357) fragment promotes AD-like pathology and cognitive impairments in vivo . Abstract: Neurite deficits and synaptic dysfunction contribute to cognitive impairments in Alzheimer's disease (AD). However, the underlying molecular mechanisms remain unclear. Here, we show that γ-adducin, a cytoskeleton-associated protein that assembles the spectrin-actin framework, is cleaved by a lysosomal cysteine proteinase named asparagine endopeptidase (AEP). AEP is upregulated and activated during aging and cleaves γ-adducin at N357, disrupting spectrin-actin assembly. Moreover, γ-adducin (1-357) fragment downregulates the expression of Rac2, leading to defects in neurite outgrowth. Expression of the γ-adducin (1-357) fragment in the hippocampus of tau P301S transgenic mice resulted in significant AD-like pathology and cognitive deficits. In summary, AEP-mediated fragmentation of γ-adducin plays a vital role in AD. Blocking the activity of AEP might be a novel therapeutic target for AD.